2022
DOI: 10.1016/j.ebiom.2021.103805
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of early antibody responses to COVID-19 mRNA vaccines in a cohort of exposed and naïve healthcare workers

Abstract: Background Two doses of mRNA vaccination have shown >94% efficacy at preventing COVID-19 mostly in naïve adults, but it is not clear if the second dose is needed to maximize effectiveness in those previously exposed to SARS-CoV-2 and what other factors affect responsiveness. Methods We measured IgA, IgG and IgM levels against SARS-CoV-2 spike (S) and nucleocapsid (N) antigens from the wild-type and S from the Alpha, Beta and Gamma variants of concern, after BNT162b2 (Pf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
69
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 47 publications
24
69
4
3
Order By: Relevance
“…Another report did not specify the enrolled population. In 17 out of 23 studies, current smokers showed significant lower antibody titre, and in a few reports, highlighted a more rapid lowering of the vaccine-elicited IgG compared with nonsmokers [19,20,[26][27][28][29][30]32,34,[36][37][38][39][40][41]43,44]. In particular, accelerated antibody decline was reported in the prospective assessments by Ferrara et al [20], Zhang et al [27], and Malavazos et al [30].…”
Section: Resultsmentioning
confidence: 92%
“…Another report did not specify the enrolled population. In 17 out of 23 studies, current smokers showed significant lower antibody titre, and in a few reports, highlighted a more rapid lowering of the vaccine-elicited IgG compared with nonsmokers [19,20,[26][27][28][29][30]32,34,[36][37][38][39][40][41]43,44]. In particular, accelerated antibody decline was reported in the prospective assessments by Ferrara et al [20], Zhang et al [27], and Malavazos et al [30].…”
Section: Resultsmentioning
confidence: 92%
“…A robust IgA and IgG response has been evoked in individuals receiving either BNT162b2 (Pfizer/BioNTech) or mRNA-1273 (Moderna) vaccination (n = 578). The neutralization was higher in mRNA-1273 vaccinees those previously had symptomatic SARS-CoV-2 infection ( Moncunill et al, 2022 ). Though the Omicron variant compromised the effectiveness of 2 doses of mRNA vaccination and reduced overall protection, it can still protect against severe consequences ( Tanne, 2021a ).…”
Section: Sars-cov-2 Vaccine Efficacy Against Omicronmentioning
confidence: 99%
“…Finally, we cannot exclude that differences in the timing of sample collection after vaccination may affect, in some cases, the variations observed in the levels of RBD-specific neutralizing antibodies between individuals within the same group. Yet, there are other factors intrinsic to the individuals that may also contribute to the heterogeneity of responses, including age, comorbidities, or smoking habits, as we have previously reported ( 21 ).…”
Section: Resultsmentioning
confidence: 77%
“…Plasma sample dilutions used reflect the different levels of neutralizing antibodies produced after vaccination as compared to those in naturally exposed individuals. These dilutions were selected based on a previous report of a cohort of healthcare workers that included the study population analyzed here, in which we evaluated the levels of neutralizing antibodies against WT RBD in SARS-CoV-2 exposed non-vaccinated subjects (after one year follow-up) and in individuals receiving the Moderna or Pfizer-BioNTech vaccines ( 21 ). Cells were stained with anti-mouse IgG-PE (Jackson ImmunoResearch), washed, and analyzed by flow cytometry using standard procedures.…”
Section: Methodsmentioning
confidence: 99%